Peningkatan Pembelajaran Biologi di Sekolah Menengah Atas Melalui Kerjasama Fakultas Kedokteran Hewan - Fajar S Permata; Analis W. Wardhana; Herlina Pratiwi; Dyah A.O.A. Pratama; Albiruni Haryo; Galuh C. Agustina; Agung P.W. Marhendra (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
Research aimed to determine the improvement in high school (SMA) biology learning outcomes through collaboration with the Faculty of Veterinary Medicine at Brawijaya University. The chosen methodology is quantitative descriptive. The collaboration commenced with an agreement between the School of Veterinary Medicine and SMAN 8 Malang. Participants included 34 11th-grade students and 3 biology teachers. The event began with an opening ceremony, followed by administering a pretest and distributing worksheets to the participants. The workshop comprised two main steps. Firstly, a seminar on various animal anatomies was conducted by faculty members from the Faculty of Veterinary Medicine, lasting for 100 minutes. Subsequently, practical sessions on bovine osteology and direct examination of animal organs, including mice, chickens, and fish, took place over 180 minutes. These practical sessions were guided by students from the School of Veterinary Medicine serving as assistants in the Anatomy Laboratory. Finally, participants underwent a posttest, completed a questionnaire, and took a group photo. Pretest and posttest scores were evaluated. The research findings indicate that the average pretest score was 25.38±4.73. Following the workshop activities, the average posttest score increased to 51.83±17.22, signifying a 100% improvement in the average posttest scores. Additionally, 18.92% of participants achieved scores exceeding 70. Based on the questionnaire, the majority of participants (55.56%) rated the collaboration activity as excellent. In conclusion, this collaboration significantly enhances biology learning in high schools, providing substantial benefits for both students and teachers. Keywords: Animal Anatomy, Veterinary Medicine, SMAN 8 Malang, Biology Workshop